Effect of a 16-Week Yoga Program on Cobb's Angle in Female Patients with Scoliosis - Mi-Young Lee; Yoonjung Park; Dong-il Seo (Asian Society of Kinesiology, 2022)
BACKGROUND Long-term postural imbalances can promote the development of diseases such as scoliosis or pain in the neck, shoulders, arms, and lumbar spine. Yoga combines exercises that target muscular strength and flexibility, suggesting that it can aid in attenuating structural and postural imbalances without the need for invasive procedures. The present study aimed to investigate the effect of a 16-week yoga program on Cobb's angle and other postural indicators in patients with scoliosis. METHODS Ten middle-aged women living in South Korea who were judged to have scoliosis based on the results of posture tests participated in a 16-week yoga program.It consisted of two 70-min sessions per week during weeks 1-4, two 80-min sessions per week during weeks 5-9, and two 90-min sessions per week during weeks 10-16. The heights of the ilium and ischium were measured to check for pelvic imbalances. Shoulder height and Cobb's angle in the spine were also assessed on radiography both before and after the intervention. RESULTS Following the 16-week program, Cobb's angle had significantly decreased from 10.50±4.26 to 7.05±3.37 (p<0.001). However, there were no statistically significant differences between pre- and post-intervention shoulder height (pre: 2.85±1.76 mm; post: 1.58±0.99 mm;p=0.124). In contrast, iliac height had decreased from 2.62±1.33 mm to 1.78±0.80 mm (p=0.048), and ischial height had decreased from 1.72±0.92 mm to 1.17±0.80 mm (p=0.043), and both differences were significant. CONCLUSIONS These results suggest that regular participation in yoga is effective for maintaining or improving postural indicatorsand attenuating imbalances in middle-aged women with scoliosis.